PENTINGNYA DANA PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN NASIONAL - Subiyanto, Subiyanto (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Education funding is crucial to improving the quality of national education. Factors play a role determining the success of education funding. Due to insufficient funds (1) facilities, infrastructure, media, learning tools, can be met, (2) the learning process can be carried out more incentive, because educators are more focused they are not looking outside the sideline, and (3) motivation and enthusiasm of personnel working to increase education, they are ready also to improve the profession. Conversely, if education funding is inadequate, resulting in ?ketersendatan? and ?inequality? in fulfillment of facilities and infrastructure, the welfare of teachers or lecturers, the level of administrative, academic and administrative services was not optimal, and the lack of passion for the professional development of teachers or lecturers and staff administrsi . This resulted in the education world work ethic is not optimal and unprofessional. Conditions and circumstances are not conducive educational institutions and professionals will not produce human resources of low quality and economic value rendah.Dalam this context that the role of the fund is one very important factor in education as an institution that requires the workings of professionalism.